CONSTRUCT INDUSTRIALIZATION STRATEGIC MODEL IN ISLAMIC PERSPECTIVE - Fauzan, Rahman (Islamic Economics and Business Faculty of UIN Antasari, 2017)
Abstract: Nowaday, there are two strategic perspective in the industialization, that are import subtitution strategic with structural perpective (Sosialism) and eksport promotion strategic with liberal perspective (Capitalism). Eventhough both of them have long been used by many countries, including Indonesia, but they have not been able to make them as the developed countries which have independence of industry and strong economic growth. This research aimed to get industrialization strategy with different perspectives, that is industrialization strategy model in Islamic perspective to create independently and strong economic growth. There are two stages in this research; the first stage is literature study to formulate the main concepts of the industrialization strategy in Islamic perspective. The second stage is to create a model of industrialization strategy ini Islamic perspective based on the formulation from the first stage. From this research showed that there are three goal of Islamic industrialization strategy they are independence, fulfillment of basic needs and defense. This research also can modeled two systems of industrialization strategy in Islamic perspective there are; the model of Industrial Funding Systems, and the model of Interaction between Resources, Industrial Type and Basic Necessities. Both models can describe the Islamic perspective of industrialization strategy in relation to independence, fulfillment of basic needs, and defense of a nation. Keywords: Construct, Model, Industrialization Strategy, Islamic Perspective, Independence, fulfillment of basic needs, defense.